Implications of anemia in patients undergoing PCI with Impella-support: insights from the PROTECT III study - Falah, Batla; Redfors, Björn; Zhao, Duzhi; Bharadwaj, Aditya S.; Basir, Mir Babar; Thompson, Julia B.; Patel, Rajan A. G.; Schonning, Michael J.; Abu-Much, Arsalan; Zhang, Yiran; Batchelor, Wayne B.; Grines, Cindy L.; et al. (Frontiers in Cardiovascular Medicine, 2024)
Background:Anemia is prevalent among patients with cardiovascular disease and is associated with adverse outcomes. However, data regarding the impact of anemia in high-risk percutaneous coronary intervention (HRPCI) are limited.To evaluate the impact of anemia in patients undergoing Impella-supported HRPCI in the PROTECT-III study.Methods:Patients undergoing Impella-supported HRPCI in the multi-center PROTECT III study were assessed for anemia based on baseline hemoglobin levels according to World Health Organization criteria. Patients were stratified into three groups: no anemia, mild anemia, and moderate or severe anemia. Major adverse cardiovascular and cerebrovascular events (MACCE: all-cause death, myocardial infarction, stroke/transient ischemic attack, and repeat revascularization) at 30 and 90 days, and major bleeding events were compared across groups.Results:Of 1071 patients with baseline hemoglobin data, 37.9% had no anemia, 43.4% had mild anemia, and 18.7% had moderate or severe anemia. Anemic patients were older and more likely to have comorbidities. Anemia was associated with higher MACCE rates at 30d (moderate to severe: 12.3%, mild: 9.8%, no anemia: 5.4%; p = 0.02) and at 90d (moderate to severe: 18.7%, mild: 14.6%, none: 8.3%; p = 0.004). These differences persisted after adjustment for potential confounders at 30 and 90d and sensitivity analysis excluding dialysis showed similar results.Major bleeding at 30d was also higher in anemic patients (5.5% vs. 1.2%, p = 0.002).Baseline anemia in Impella-supported HRPCI is common, and independently associated with MACCE and major bleeding, emphasizing its significance as a prognostic factor. Specific management strategies to reduce anemia-associated MACCE risk after HRPCI should be examined.